Tingkat Kesediaan dan Ekspektasi Kompensasi Konsumen dalam Pengumpulan Limbah Popok Bayi - Sri Purwati, Purwati; Nancy Oktyajati; Ica Salsa Bila (Program Studi Teknik Industri Universitas Setia Budi, 2024)
Baby diaper waste management is becoming an increasingly pressing environmental issue due to the high use of disposable diapers in the community. The lack of waste management infrastructure and low environmental awareness are the main obstacles in increasing public participation in the collection of baby diaper waste. This study aims to identify the factors that influence the level of consumer willingness to collect baby diaper waste and determine the expected compensation expected by consumers. Multiple ordinal regression and Contingent Valuation Method (CVM) were used to achieve these objectives. The results of multiple ordinal regression analysis show that several independent variables have a significant influence on community participation in baby diaper waste management, including Environmental Awareness (X1), Infrastructure Availability (X2), Knowledge and Education (X3), Economy (X4), Policy and Regulation (X6), Ease of Access and Facilities (X7), and Culture and Social Norms (X8). Meanwhile, Community Involvement (X5) did not show a significant effect. Of these variables, Infrastructure Availability (X2), Culture and Social Norms (X8), and Policy and Regulation (X6) show the most significant influence. Based on the CVM results, the average expected compensation for community participation is Rp1,250 per kilogram of dry diaper waste. These findings suggest the importance of improving waste management infrastructure as well as supportive policies to encourage community participation. In addition, attractive economic incentives need to be implemented to strengthen community involvement in the collection of baby diaper waste. This study provides insights for stakeholders in formulating policies that support the development of effective and sustainable community participation-based waste management programs.